Fun Learning Activity untuk Memotivasi Belajar Anak pada Siswa Kelas III SDN 6 Tanjung Lago - Mutia Mawardah; Vini Ina Safitri (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Fun learning is a learning approach that emphasizes a fun and interactive learning process that can increase student engagement and motivation. In general, fun learning can be defined as a learning strategy that creates an effective and engaging learning atmosphere, by utilizing games, interactive media, and fun activities so that the learning process does not only focus on receiving material, but also on students' direct experience in constructing their own knowledge. This method has been initiated by educators as a way to make learning more interesting and can improve overall student learning achievement starting from Observation and Introduction to the Environment, Design and Preparation of Fun Learning Media, Implementation of Fun Learning Activities, Reflection and Simple Evaluation and Preparation of Final Reports. The results of this activity The use of the Fun Learning Activity method also shows that fun learning can create a warm and comfortable classroom climate. Students who initially tended to be shy, hesitant, or lacked confidence, gradually began to dare to express themselves, interact in English, and follow teacher instructions with enthusiasm. These interactive activities allow students to learn through direct experience, so that the knowledge gained becomes more embedded and can be applied in relevant contexts.